Implementing throwaway prototyping model in web development life cycle (WDLC) - Abdullasim, Nazreen (2009)
The purpose of this study is to analyze the relationship between web development life cycle (WDLC) and system development life cycle (SDLC). Even though the two terms WDLC and SDLC are similar in a sense that both discuss about development lifecycle but they have differences in term of its scope. From the term WDLC itself has shows that it is focusing on website development meanwhile SDLC is focusing on software at large. Website can be considered as a subset of software. Therefore, the study is about analyzing how far WDLC relevancy compares to SDLC. SDLC comprises of methodologies such as structured development, rapid application development, and agile development. In each methodology comprises of many SDLC models which complying with specific software development trends. Hence by analyzing typical website development trends and characteristic will allows to identify the suitable SDLC model. Introducing the model only will not sufficient if there is no guideline of how to apply it. Therefore the study also covers the implementation of the model with the web development processes.